(untitled) (Revista cientifica In Vestigium Ire, 2020)
Over the years, digital marketing has increased its participation in small and medium-sized enterprises in the city of Tunja, partly because it has been demanded by the same market that is increasingly being modernized and strengthened in terms of techniques that allow to have a closer to the customer outreach and a satisfaction of the same much sooner. Growing technological advances have led to big changes in consumers and entrepreneurs, including the way marketing strategies are executed. Thanks to this comes the now known e-commerce and digital marketing. What is sought with the results of this research is that interested Tunja City entrepreneurs can determine and use the relevant marketing strategies to be done on Instagram in the best possible way, in order to increase their sales.